Eco-friendly microwave synthesis of Mg(ii) phenoxy carboxylic acid coordination compounds with specific motifs driven by multiple hydrogen bonding. Issue 72 (15th July 2016) - Xu, Xiuling; Hu, Fan; Yan, Saisai; Lin, Jianguang; Li, Qing; Shuai, Qi
Abstract : Four magnesium complexes with specific motifs driven by multiple hydrogen bonding were synthesized by microwave method. The design strategy presented here gave an insight into the further structural prediction of magnesium supramolecular assemblies. Abstract : Four novel Mg(ii ) coordination compounds [Mg(CPA )2 (H2 O)4 ]1, [Mg(H2 O)6 ]·(MCPA )2 2, [Mg(DCPA )(H2 O)5 ]·(DCPA )3 and [Mg(TCPA )2 (H2 O)4 ]·2H2 O4 were designed by the strategy of hydrogen bonding driven self-assembly (HCPA = 2-chlorophenoxyacetic acid, HMCPA = 2-methyl-4-chlorophenoxyacetic acid, HDCPA = 2, 3-dichlorophenoxyacetic acid andHTCPA = 2, 4, 6-trichlorophenoxyacetic acid). Single-crystal X-ray diffraction demonstrated that each coordination compound had its own specific motif driven by multiple hydrogen bonding: rectangle motif (compound1 ), butterfly motif (compound2 ), head and tail connected double heart-rectangle motif (compound3 ) and alternative one side shared hexagon-rectangle motif (compound4 ). The hydrogen bonding effects (O–H⋯Cl and O–H⋯O) on thermostability of the title compounds were well proved by TG analysis. The antibacterial activity of1–4 has been explored, and all of them showed antibacterial efficiency against colibacillus at certain concentrations. The number of chlorides in the ligands seemed to affect the efficiency of the complexes while their position had no obvious effect. In addition, all the title compounds were evaluated for plant growth regulation by using the lettuce seedling growth bioassay. The results showed that these kinds of compounds had potential to serve as natural plant growth regulators because of their higher allelopathic activity. This research firstly applied the effective microwave method to synthesize Mg(ii ) phenoxy carboxylic acid coordination compounds. The design strategy of hydrogen-bonding-driven self-assembly presented here gave a novel insight into the further structural prediction and biofunction achievement of Mg(ii ) supramolecular assemblies.